Reflections on the promotion of Active Aging - Pedro, Wilson José Alves (2014)
From the international guidelines on Active Aging, this study examines some of these developments in the state of São Paulo, as well as strategies deployed within the state, in the region of the Regional Health Department III - Araraquara the State Department of Health This region has an aging population of 12.05%. This is an exploratory and descriptive. Through documentary analysis identified strategies deployed in several areas.